Relation between natural regeneration of forest trees and shrubs species and environmental factors in protected area of western Dena (Posht kareh) - Roghayyeh Zolfaghari; Seyyed Moeinoddin Zamani (تحقیقات جنگل و صنوبر ایران, 2016)
Concerning the importance of tree and shrub regeneration and its effect on the feature of forests, the present study was designed to evaluate the regeneration of forest species and its relationship with environmental factors in Dena protected area. To this aim, 50 plots of 450 m2 each were selected in a randomly- systematic design based on a 500 × 250 m grid. Then the regeneration of species in three different height classes (< 30 cm, 130-30 cm, and > 130 cm) was counted. The results showed that the regeneration of different species was affected by various environmental factors. Among the physiographic factors, height had the greatest impact on regeneration, i.e. increasing the height from sea level leads to reducing the regeneration of Quercus brantii, Cerasus microcarpa, and Daphne mucronata, Whereas Amygdalus reuteri and Lonicera nummulariifolia showedincrease ofregeneration. However, the regeneration of Q. brantii and C. microcarpawas was higher in medium slopes on northern aspects. The results of soil elements also showed positive correlation between that soil nitrogen levels were with C. microcarpa regeneration and negatively correlated between L. nummulariifolia and soil nitrogen levels. On the other hand the correlation results revealed that the association of Q. brantii and C. microcarpa occurs jointly in low altitudes, while association of A. reuteri and L. nummulariifolia jointly occurs across high altitudes. Also regenerations of Pistacia atlantica and A. scoparia were observed to be jointly, similar to those of A. orientalis and L. nummulariifolia. Finally, the anthropogenic and environmental factors as well as the competition between species are concluded to affect the regeneration of variety of forest species.